Strategi Bertahan Hidup Tukang Becak Menghadapi Persaingan Transportasi Di Banda Aceh - Liza Ikhsana; R. A. Alivia Yuningrum; Najwa Rusydi; Sevtia Husna Anggreini; Ibnu Phonna Nurdin (Universitas Palangka Raya, 2024)
The increasingly modern technological development brings blessings to some societies but also has a negative impact on other societies in this way. The tradesman, in carrying out his current job, is competing with other means of transport, which has an impact on the decrease in the turnover of tradesmen's transport services. The purpose of this research is to look at the form of survival strategies in the midst of such unfavorable conditions. The research was conducted by the Kuta Alam District of Banda Aceh. This study uses a qualitative approach to case studies. The research data was obtained through observations and in-depth interviews. The in-depth interview involved five informants based on criteria of at least five years of experience working as a scavenger and having been over 30 years of age. The results of the research showed a variety of obstacles faced by the craftsman in carrying out his profession: a. decreased earnings; b. the intensity of interaction is decreasing; c. inability to compete with the online fleet; d. productivity of work is declining. Therefore, the beacon is looking for a strategy to keep them alive: a. popularizing the name beacons according to the authority held by the province of Aceh (enforcing the Islamic Shariah); b. diversification of livelihoods, which is a double livelihood pattern run by beacones to cover a lack of income in carrying out their main profession. Despite having developed some strategies, the scout is still in an unfavorable condition. Thus, it can be concluded that the presence of the predicted scoundrel will fade more and more in the future.